Mixed Stocking by Cattle and Goats for Blackberry Control in Rhizoma Peanut–Grass Pastures. Issue 6 (1st November 2014) - Krueger, N.C.; Sollenberger, L.E.; Blount, A.R.; Vendramini, J.M.B.; Lemos, N.L.S.; Costa, A.G.; Adesogan, A.T.
ABSTRACT: Blackberry ( Rubus fruticosas L.) can be a weed in rhizoma peanut ( Arachis glabrata Benth.)–grass pastures. Goats ( Capra hircus ) have provided effective control of Rubus spp. in other environments, but their efficacy has not been tested in legume‐grass swards in this context. The objective was to evaluate rotational stocking by goats alone or with cattle ( Bos spp.) for blackberry control. Treatments stocked at 2.6 animal units (AU) ha −1 included a cattle‐alone control, goats alone, concurrent stocking of cattle and goats, sequential stocking of cattle followed by goats, and sequential stocking of goats followed by cattle. The final treatment was concurrent stocking at a stocking rate of 3.5 AU ha −1 . Goats grazed blackberry readily, but cattle avoided it. Blackberry selection was greatest when goats followed cattle sequentially. The blackberry proportion of total biomass increased 10% when cattle grazed alone but was reduced 11% with goats alone and 13% with mixed concurrent grazing at a high stocking rate. Treatments including goats resulted in reductions or smaller increases in blackberry mass than for cattle alone. Goats alone or with cattle resulted in greater removal of blackberry leaf and in reduced height and stem density than cattle alone. Goats reduced the blackberry contribution more than cattle, but it was not eliminated from initially heavily infested pastures across 2 yr of grazing. A greater goat stocking rate or a combination of grazing and mowing may be needed for complete eradication.